1994
DOI: 10.1159/000098636
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Central (Thalamic) Pain: Combined Change of Sensory Thalamus with Cerebral Cortex around Central Sulcus

Abstract: In 13 patients with central (thalamic) pain after stroke, CT, MRI, PET scan and intraoperative thalamic microrecordings were performed. Electrophysiological studies showed that irregular burst discharges were often encountered in the posterolateral thalamus. The more often the irregular burst discharges were encountered, the greater the decrease of sensory response in the posterolateral thalamus. Metabolic studies showed that regional cerebral glucose metabolism decreased in both the posterolateral thalamus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 0 publications
2
21
0
2
Order By: Relevance
“…moved slowly" over the skin. When this stimulus was used on the affected side, it produced activation of structures very similar to those activated in response to 20°C waterbath stimulation of the affected hand in the present study (Table 4) (Peyron et al, 1998) (see also Cesaro et al, 1991;Hirato et al, 1994).…”
Section: Functional Imaging Studiessupporting
confidence: 63%
“…moved slowly" over the skin. When this stimulus was used on the affected side, it produced activation of structures very similar to those activated in response to 20°C waterbath stimulation of the affected hand in the present study (Table 4) (Peyron et al, 1998) (see also Cesaro et al, 1991;Hirato et al, 1994).…”
Section: Functional Imaging Studiessupporting
confidence: 63%
“…The decrease in basal activity in the thalamus is not unexpected, as thalamic dysfunction has long been thought to play a role in chronic pain. Clinical studies have reported spontaneous pain and disturbed sensations produced by thalamic lesions (Riddoch, 1938;Garcin et al, 1968) and several recent PET studies have demonstrated that there is reduced thalamic rCBF and/or regional glucose metabolism in patients with chronic pain (Canavero et al, 1993;Hirato et al, 1993Hirato et al, ,1994Iadarola et al, 1995;Hsieh et al, 1995). It is possible that thalamic rCBF is down because of reduced inhibitory background activity, but this cannot be proved based on this study.…”
Section: Discussionmentioning
confidence: 77%
“…19) Irregular burst discharges were found in the posterolateral thalamus in patients with CPSP, and regional cerebral glucose metabolism decreased in the thalamus and cortical postcentral area, but increased in the cortical precentral area, suggesting that changes in cortical activity adjacent to the central sulcus might be related to the genesis of thalamic pain. 6) Differences in abnormal activities in the thalamic neurons and changes in cortical and thalamic activity may be one reason for the necessity of higher intensity stimulation parameters for MCS in the brainstem-spinal group.…”
Section: Discussionmentioning
confidence: 99%